Effect of liquid biofertilizers under varying fertility levels on potassium and sulphur concentration & uptake in Chickpea (Cicer arietinum L.) - Om Prakash Prajapat; Surendra Singh; Lala Ram Yadav (Annals of Agricultural Research, 2024)
To evaluate the impact of liquid biofertilizers under different fertility levels on the uptake of potash (K) and sulphur (S) in seed and straw in chickpea, a field experiment was conducted in the rabi season of 2015–16 and 2016–17 at the crop research farm, Rajasthan agricultural research institute, Durgapura, Jaipur. Experiment consisted of four fertility levels (control, 50% N + 75% P2O5 + 75% K2O + 50 % S, 75% N + 85% P2O5 + 85% K2O + 75 % S and 100% NPKS) and seven biofertilizer i.e. Control, Rhizobium, PSB (P-solubilizer) +PMM P-mobilizer), KMB (K-mobilizer), Rhizobium + PSB+PMM + KMB, SSB (S-solubilizer), Rhizobium + PSB + PMM + KMB + SSB) were laid out in split plot design with three replication. The 28 treatment combinations used in the experiment. Results revealed that 100% NPKS improved the K and S content in seed of chickpea by 10.0% and 12.6%, respectively, over control. Similarly, same treatment increased the K and S content in chickpea straw by 10.8% and 12.8%, respectively, compared to control. In case of bio-fertilizers, Rhizobium + PSB + PMM + KMB + SSB along with 100% NPKS augmented the K and S content in seed by 8.55% and 10.8%, respectively over control. Therefore, it could be concluded that Rhizobium + PSB + PMM + KMB + SSB along with 100% NPKS should be recommended to the farmer for better crop quality.